ANÁLISE DO NÍVEL DE MATURIDADE TECNOLÓGICA DE UM BANHEIRO SECO CAPAZ DE COLETAR E TRATAR SEPARADAMENTE URINA E FEZES HUMANAS - Ramos, Breno Simões (2021)
This research aimed to evaluate the acceptance of users and the level of technological maturity of a bathroom capable of collecting feces and urine separately without the need for water discharge. The dry sanitary basin (BSS) is a technological innovation capable of recovering nutrients from the treatment of human excreta, in addition to promoting environmental preservation of natural resources, mainly related to the large water consumption of the current sanitation model. it is necessary to evaluate the degree of maturity of this technology, through a specific methodology called techonology readniless level and the behavior of users when they are in contact with BSS. Specific tests for odor monitoring, accessibility and usability, temperature monitoring were carried out. and humidity and monitoring the bathroom use panel. The tests show that the technology has a satisfactory degree of maturity, reaching stage 8 (TRL 8). Furthermore, user acceptance was unanimous on the part of everyone involved in the research.